Secondary battery and its manufacturing method
By introducing a crosslinking matrix into the lithium-ion battery, the adhesion between the negative electrode and the separator is enhanced, and the separator crack problem caused by volume expansion of the silicon-based negative electrode is solved, and the adhesion and life of the battery are improved.
Patent Information
- Application Number
- JP2024541153
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-17
- Filing Date
- 2023-10-18
- Publication Date
- 2025-02-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In existing lithium-ion batteries, the volume expansion of the silicon-based negative electrode material during charging and discharging causes the adhesion between the negative electrode and the separator to decrease, causing cracks in the separator layer, reducing battery capacity and increasing internal resistance.
A bonding layer containing the first and second repeating units is introduced between the negative electrode and the separator, and a crosslinking matrix is formed using a binder polymer and a crosslinking agent to enhance the adhesion between the negative electrode and the separator.
Effectively prevent the negative electrode from over-expansion during charging and discharging, reduce cracks in the diaphragm layer, and improve the adhesion and life of the battery.
Smart Images

Figure 2025503640000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention claims the benefit of the filing date of Korean Patent Application No. 10-2022-0134317 filed with the Korean Intellectual Property Office on October 18, 2022, and Korean Patent Application No. 10-2023-0139006 filed with the Korean Intellectual Property Office on October 17, 2023, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a secondary battery and a method for manufacturing the same. [Background technology]
[0003] Lithium-ion batteries, a representative example of secondary batteries, are basically composed of a positive electrode, a separator, a negative electrode, and an electrolyte, and are a representative energy device with high energy density that can be charged and discharged while reversibly converting chemical energy and electrical energy, and are widely used in small electronic devices such as mobile phones and notebook computers. Recently, in response to environmental issues, high oil prices, and energy efficiency and storage, their application to hybrid electric vehicles (HEVs), plug-in electric vehicles (Plug-in EVs), electric bikes (E-bikes), and energy storage systems (ESSs) is rapidly expanding.
[0004] Lithium-ion batteries are stable electrochemical devices insulated by a separator. However, internal or external abnormal phenomena or impacts on the battery can cause a short circuit between the positive and negative electrodes, which can lead to heat generation and explosion. Therefore, ensuring the thermal and chemical safety of the separator as an insulator is a matter that must be considered with the utmost importance.
[0005] Silicon is the most promising high-capacity anode active material, and is abundant in resources. When reacted with lithium, it has a theoretical maximum capacity of 4,200mAhg. -1 (3,579mAhg -1, @RT), it has 10 times the capacity of graphite, and negative electrode active materials using this are being developed. However, silicon active material particles have problems such as the collapse of the active material structure due to a 300% or more volume expansion when reacting with lithium, and the deterioration of the electrode life characteristics due to electrical contact loss caused by the active material being detached from the current collector. In addition, cracks occur in the coating layer of the separator during discharge, reducing the efficiency of the battery, as well as the degeneration of the cell and increasing resistance. Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a secondary battery capable of increasing the adhesive strength between a negative electrode and a separator on an electrolyte.
[0007] Another object of the present invention is to provide a secondary battery capable of solving the problems of anode peeling caused by volume expansion of a silicon-based anode active material and a decrease in battery capacity caused by cracks in a coating layer of a separator.
[0008] It is still another object of the present invention to provide a method for producing the secondary battery.
[0009] The object of the present invention is not limited to the object mentioned above, and other objects and advantages of the present invention not mentioned can be understood from the following description and will be more clearly understood by the embodiment of the present invention. Also, it should be easily understood that the object and advantages of the present invention can be realized by the means and combinations thereof as set forth in the claims. [Means for solving the problem]
[0010] According to a first aspect of the present invention to achieve the above object, there is provided a secondary battery including an anode, a cathode, a separator interposed between the anode and the cathode and including a porous substrate and a coating layer disposed on at least one surface of the porous substrate, and an electrolyte, wherein the anode includes a binder polymer including a first repeat unit, the coating layer includes a second repeat unit, and the first repeat unit and the second repeat unit are bonded to each other. Here, the first and second repeat units being bonded to each other may mean, for example, that the respective repeat units are bonded to each other through a covalent bond.
[0011] According to a second aspect of the present invention, in the first aspect, the negative electrode can include silicon-based active material particles.
[0012] According to a third aspect of the present invention, in the first or second aspect, the binder polymer may include polyacrylamide.
[0013] According to a fourth aspect of the present invention, in any one of the first to third aspects, the coating layer may be disposed between the negative electrode and the porous substrate.
[0014] According to a fifth aspect of the present invention, in any one of the first to fourth aspects, the second repeat unit may be derived from a crosslinking agent.
[0015] According to a sixth aspect of the present invention, in the fifth aspect, the crosslinking agent may be a compound containing carbon-carbon double bonds at both terminals.
[0016] According to a seventh aspect of the present invention, in the sixth aspect, the crosslinking agent may be one or more selected from the group consisting of N,N'-methylenebisacrylamide, N,N'-bisacrylylcystamine, and N,N'-diallyltartardiamide.
[0017] According to an eighth aspect of the present invention, in any one of the first to seventh aspects, the first repeat unit and the second repeat unit form a crosslinked matrix, and a degree of crosslinking of the crosslinked matrix may be 5 to 15%.
[0018] According to a ninth aspect of the present invention, in any one of the first to eighth aspects, an adhesive strength of the negative electrode to the separator may be 10 to 15 gf / 20 mm.
[0019] In any one of the first to ninth aspects, the second repeat unit may be the same as or different from the first repeat unit, specifically different.
[0020] According to a tenth aspect of the present invention, there is provided a method for manufacturing a secondary battery, the method including: coating at least one surface of a porous substrate with a composition for forming a coating layer, followed by drying to form a separator; and forming a negative electrode of a negative electrode slurry on one surface of the separator, the composition for forming a coating layer including an initiator and a crosslinker, and the negative electrode slurry including a binder polymer.
[0021] According to an eleventh aspect of the present invention, in the tenth aspect, the content of the crosslinking agent may be 0.01 to 0.10 parts by weight based on 100 parts by weight of the binder polymer.
[0022] According to a twelfth aspect of the present invention, in the tenth or eleventh aspect, the content of the binder polymer may be 5 to 15 wt % based on the weight of a total solid content included in the negative electrode slurry.
[0023] According to a thirteenth aspect of the present invention, in any one of the tenth to twelfth aspects, the composition for forming a coating layer may further include a polymerization reaction catalyst.
[0024] According to a fourteenth aspect of the present invention, there may be provided a method for manufacturing a secondary battery in any one of the tenth to thirteenth aspects, further comprising the steps of: forming a positive electrode on another surface of the separator to manufacture an electrode assembly; inserting the electrode assembly into a battery case, and injecting an electrolyte into the battery case; and placing the battery case containing the electrolyte in a chamber at 40 to 80° C. to carry out a crosslinking reaction.
[0025] The above-mentioned solutions to the problems are not exhaustive. The various features of the present invention and the attendant advantages and effects will be more fully understood with reference to the following specific embodiments. Effect of the Invention
[0026] According to one aspect of the present invention, a secondary battery capable of increasing the adhesive strength between a negative electrode and a separator on an electrolyte can be provided.
[0027] According to another aspect of the present invention, a secondary battery is provided that solves the problems of a decrease in electrode life characteristics due to volume expansion of a silicon-based negative electrode active material and a decrease in battery efficiency due to cracks occurring in a coating layer of a separator during discharge.
[0028] The above-mentioned effects and the specific effects of the present invention will be described below together with the specific contents for carrying out the invention. [Brief description of the drawings]
[0029] [Figure 1] 1A and 1B are schematic diagrams of secondary batteries according to a comparative example and an example.
[0030] [Diagram 2] 2 is a schematic diagram illustrating cross-linking between a binder polymer and a cross-linking agent according to an embodiment of the present invention; FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] Hereinafter, each component of the present invention will be described in more detail so that a person having ordinary knowledge in the technical field to which the present invention belongs can easily implement the present invention. However, this is merely an example, and the scope of the present invention is not limited to the following content.
[0032] The configuration of the present invention will be described in further detail below with reference to FIG.
[0033] FIG. 1 is a schematic diagram of secondary batteries according to the comparative example and the embodiment.
[0034] 1(a), a secondary battery 90 according to the comparative example may include an anode 10' including an anode current collector 10a' and an anode active material layer 10b' disposed on both sides of the anode current collector 10a', a cathode 30' including a cathode current collector 30a' and a cathode active material layer 30b' disposed on both sides of the cathode current collector 30a', and a separator 20' interposed between the anode 10' and the cathode 30'. During charging of the secondary battery, lithium ions are inserted into silicon-based anode active material particles in the anode, causing a volume expansion problem of the anode, and during discharging, cracks may occur in the anode active material layer or the anode may peel off.
[0035] Referring to FIG. 1(b), a secondary battery 100 according to the present invention includes an anode 10, a cathode 30, a separator 20 interposed between the anode 10 and the cathode 30, and an electrolyte (not shown).
[0036] According to one aspect of the present invention, there is provided a secondary battery including an anode, a cathode, a separator interposed between the anode and the cathode and including a porous substrate and a coating layer disposed on at least one surface of the porous substrate, and an electrolyte, wherein the anode includes a binder polymer including a first repeating unit, the coating layer includes a second repeating unit, and the first repeating unit and the second repeating unit are bonded to each other. Specifically, the second repeating unit may be derived from a crosslinking agent, and the second repeating unit may be the same as or different from the first repeating unit. According to one aspect of the present invention, a binder polymer that forms a chemical crosslink with the composition for forming a coating layer is added to an anode slurry, and a crosslinking agent is added to the composition for forming a coating layer, whereby the binder polymer and the crosslinking agent react with each other to form a crosslinked matrix at the interface between the anode and the coating layer. The crosslinked matrix is formed between the interface between the anode and the coating layer of the separator, and thus the adhesive strength between the anode and the separator on the electrolyte can be significantly increased.
[0037] 1. Secondary battery
[0038] negative electrode 10
[0039] The anode 10 according to the present invention includes an anode active material that generates electricity by storing or releasing lithium ions released from the cathode. The anode active material stores lithium ions in the anode during charging, and transfers the lithium ions to the cathode via the electrolyte during discharging, and electrons separated from the lithium ions move along the conductor to generate electricity.
[0040] The negative electrode active material according to the present invention can include at least one of silicon-based active material particles and graphite-based active material particles, and specifically can include silicon-based active material particles. Silicon active material particles have problems such as structural collapse of the active material due to a volume expansion of 300% or more during the reaction with lithium in the charging process and detachment of the active material from the current collector, resulting in a decrease in the life characteristics of the electrode due to electrical contact loss. In the discharging process, not only does cracking occur in the coating layer of the separator, leading to a decrease in battery efficiency, but there is also a problem that the cell deteriorates and the resistance increases. According to an embodiment of the present invention, by forming a crosslinked matrix on the interface between the negative electrode and the coating layer contained in the separator, it is possible to effectively prevent the negative electrode from excessively expanding in volume during the charging process, and by effectively preventing cracks from occurring in the coating layer of the separator during the discharging process, it is possible to prevent an increase in resistance due to cell deterioration.
[0041] For example, the silicon-based active material particles are Si, SiO x (0 < x ≦ 2), Si-C composite, and Si-Y alloy (Y is any one element selected from the group consisting of alkali metals, alkaline earth metals, transition metals, group 13 elements, group 14 elements, and rare earth elements), and one or more selected from the group can be used.
[0042] The average size (D 50 ) of the silicon-based active material particles can be 1 to 100 μm, and specifically can be 5 to 30 μm. When the average size of the silicon-based active material particles satisfies the above numerical range, the battery capacity can be sufficiently increased.
[0043] For example, the graphite-based active material particles can include one or more selected from the group consisting of artificial graphite, natural graphite, graphitized carbon fiber, and graphitized graphite mesocarbon microbeads.
[0044] For example, the content of the negative electrode active material can be 80 to 97% by weight based on the total solid content contained in the negative electrode active material layer described later.
[0045] The negative electrode according to the present invention includes a binder polymer, and the binder polymer may include a first repeating unit. The binder polymer applied to the negative electrode according to the present invention can suppress separation between negative active material particles or between a negative active material layer and a current collector. Specifically, the binder polymer may be a rigid type binder capable of reducing the volume expansion of the negative electrode, and more specifically, may include a first repeating unit in which a binder monomer is polymerized. Specifically, the first repeating unit not only serves as a binder in the negative electrode to suppress separation between negative active material particles or between a negative active material layer and a current collector, but also effectively prevents volume expansion of silicon-based negative active material particles due to the structural characteristics of the rigid type.
[0046] Specifically, the binder polymer may include polyacrylamide. Specifically, the weight average molecular weight (Mw) of the polyacrylamide may be 500,000 to 1,500,000 g / mol, more specifically, 700,000 to 1,000,000 g / mol. Acrylamide, which is a monomer of the polyacrylamide, contains a carbon-carbon double bond (C=C) that can react with a crosslinking agent, so that in the presence of an initiator, a crosslinking reaction with the crosslinking agent can occur through a radical mechanism.
[0047] According to yet another embodiment of the present invention, the binder polymer may further include another binder polymer in addition to the polyacrylamide. Examples of the other binder polymers include poly(vinylidene fluoride co-hexafluoropropylene), poly(vinylidene fluoride-co-trichloroethylene), poly(methylmethacrylate), poly(ethylhexylacrylate), poly(butylacrylate), poly(acrylonitrile), poly(vinylpyrrolidone), poly(vinylacetate), ethylene-vinylacetate copolymer (poly(ethylene-co-vinylacetate)), poly(ethylene oxide), polyacrylate, cellulose acetate, and cellulose acetate butyrate. Examples of suitable cellulose acetate copolymers include, but are not limited to, cellulose acetate propionate, cyano ethyl pullulan, cyano ethyl poly(vinylalcohol), cyanoethylcellulose, cyanoethylsucrose, pullulan, styrene-butadiene rubber, and carboxyl methyl cellulose.
[0048] The negative electrode 10 according to the present invention may include a negative electrode current collector 10a and a negative electrode active material layer 10b disposed on at least one surface of the negative electrode current collector 10a. The negative electrode active material layer may include the negative electrode active material, a conductive material, and a negative electrode binder.
[0049] The negative electrode current collector 10a may function as a passageway for transferring electrons from the outside or receiving electrons from the negative electrode active material to the outside so that an electrochemical reaction occurs in the negative electrode active material. For example, the negative electrode current collector may be made of copper, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., and specifically, transition metals that easily adsorb carbon, such as copper and nickel, may be used as the current collector. For example, the thickness of the negative electrode current collector may be 6 μm to 20 μm, but the thickness of the negative electrode current collector is not limited thereto.
[0050] The conductive material can improve the conductivity between active material particles or between the active material particles and the metal current collector in the electrode and prevent the binder from acting as a non-conductor. The conductive material can be, for example, one or a mixture of two or more conductive materials selected from the group consisting of graphite, carbon black, carbon fiber, metal fiber, metal powder, conductive whiskers, conductive metal oxide, activated carbon, and polyphenylene derivatives, and more specifically, one or a mixture of two or more conductive materials selected from the group consisting of natural graphite, artificial graphite, Super-p, acetylene black, Ketjen black, channel black, furnace black, lamp black, summer black, Denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate, and titanium oxide.
[0051] If necessary, the negative electrode active material layer may further include an additive, which may be, for example, at least one selected from the group consisting of a dispersant, a plasticizer, an antioxidant, an active agent, a stabilizer, and an antistatic agent.
[0052] Separation membrane 20
[0053] 1, the separator 20 according to the present invention is interposed between the negative electrode 10 and a positive electrode 30 described below, and includes a porous substrate and a coating layer disposed on at least one surface of the porous substrate. Specifically, the coating layer may be disposed between the negative electrode and the porous substrate. By disposing the coating layer between the negative electrode and the porous substrate, a cross-linked matrix may be formed at the interface between the negative electrode and the coating layer, thereby increasing the adhesion of the negative electrode to the coating layer on the electrolyte.
[0054] The coating layer according to the present invention may include all solids except for the solvent, obtained by drying the composition for forming a coating layer.
[0055] The second repeat unit according to the present invention may be derived from a cross-linking agent. The second repeat unit may be the same or different from the first repeat unit, and may be specifically different.
[0056] The composition for forming a coating layer according to the present invention includes a crosslinking agent that crosslinks with the binder polymer contained in the negative electrode. The crosslinking agent crosslinks with the binder polymer contained in the negative electrode to form a crosslinked matrix at the interface between the negative electrode and the coating layer. The crosslinked matrix is formed at the interface between the negative electrode and the coating layer of the separator, thereby significantly increasing the adhesive strength between the negative electrode and the separator on the electrolyte.
[0057] Specifically, the crosslinking agent may be a compound containing a carbon-carbon double bond (C=C) at both ends, and more specifically, a compound containing a carbon-carbon double bond at both ends and at least one amide group in an internal chain. The crosslinking agent may be, for example, one or more selected from the group consisting of N,N'-methylenebisacrylamide, N,N'-bisacrylylcystamine, and N,N'-diallyltartardiamide, and may be N,N'-methylenebisacrylamide. According to some embodiments of the present invention, when N,N'-methylenebisacrylamide is used as the crosslinking agent, the adhesive strength between the anode and the separator can be increased compared to other types of crosslinking agents.
[0058] According to another embodiment of the present invention, the first repeating unit and the second repeating unit are bonded to each other to form a crosslinked matrix, and the degree of crosslinking of the crosslinked matrix may be 5 to 15%, specifically 7 to 12%. When the degree of crosslinking of the crosslinked matrix is within the above numerical range, the adhesive strength of the negative electrode and the separator on the electrolyte is sufficiently improved, and at the same time, the chemical crosslinking between the negative electrode and the coating layer can suppress the occurrence of cracks due to the contraction / expansion of the negative electrode, thereby improving the performance of the secondary battery. The degree of crosslinking of the crosslinked matrix can be analyzed by using the Ninhydrin (2,2-dihydroxy-1,3-indanedione) analysis method described in Journal of the Taiwan Institute of Chemical Engineers Volume 72, March 2017, Pages 182-193. For example, the freeze-dried gel is crushed into a sample of 5 mg. After adding 1 ml of ninhydrin solution (1.5% (w / v) in ethanol) to the sample, the prepared mixture is heated at 80° C. for 25 min. The heated mixture is cooled to room temperature for 1 h, and the cooled mixture is diluted with water. The degree of crosslinking of the crosslinked matrix can then be calculated by measuring the optical absorbance of the crosslinked and non-crosslinked gels at λ=570 nm using a PerkinElmer Lambda 35 UV-visible spectrometer.
[0059] [Formula 1]
[0060] Degree of cross-linking of cross-linked matrix (%) = {1-(absorbance of cross-linked gel / absorbance of non-cross-linked gel) x 100}
[0061] In one example, the crosslinked matrix can proceed as shown in Reaction Scheme 1 below.
[0062] [Reaction Scheme 1]
[0063] [ka]
[0064] FIG. 2 is a schematic diagram illustrating how a binder polymer and a crosslinking agent according to one embodiment of the present invention are crosslinked with each other.
[0065] Referring to Reaction Scheme 1 and FIG. 2, under the condition of an initiator (ammonium sulfate) and a polymerization catalyst (tetramethylethylenediamine (TEMED)), the crosslinked matrix may include a first repeating unit formed by polymerization of acrylamide, which acts as a binder monomer in the negative electrode, and a second repeating unit derived from N,N'-methylenebisacrylamide, which acts as a crosslinking agent in the coating layer of the separator.
[0066] The coating layer according to the present invention may include inorganic particles that contribute to improving the mechanical strength and heat resistance of the separator for a secondary battery. In particular, the inorganic particles are not particularly limited as long as they are electrochemically stable. That is, the inorganic particles that can be used in the present invention are those that are suitable for use in the operating voltage range (e.g., Li / Li + There are no particular limitations as long as the oxidation and / or reduction reaction does not occur at a reference voltage of 0 to 5 V.
[0067] For example, when inorganic particles having a high dielectric constant are used as the inorganic particles, the inorganic particles can contribute to increasing the dissociation degree of the electrolyte salt, for example, the lithium salt, in the liquid electrolyte, thereby improving the ionic conductivity of the electrolyte. For the above reasons, the inorganic particles may be inorganic particles having a dielectric constant of 5 or more, inorganic particles having lithium ion transfer ability, or a mixture thereof.
[0068] The inorganic particles having a dielectric constant of 5 or more are Al2O3, SiO2, ZrO2, AlO(OH), Al(OH)3, Mg(OH)2, BaSO4, TiO2, BaTiO3, Pb(Zr x Ti 1-x )O3(PZT, where 0 <x<1)、Pb1-x La x Zr 1-y Ti y O3 (PLZT, where 0 < x < 1, 0 < y < 1), (1 - x)Pb(Mg 1 / 3 Nb 2 / 3 )O 3-x PbTiO3 (PMN - PT, where 0 < x < 1), HfO2, SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, and SiC, and can be one or more mixtures selected from the group consisting of them.
[0069] The inorganic particles having the lithium ion transfer ability are lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y -based glass (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), lithium germanium thiophosphate (Li x Ge y P z S w , 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitride (Li x N y , 0 < x < 4, 0 < y < 2), SiS2 - based glass (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4) and P2S5 - based glass (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7), and can be one or more mixtures selected from the group consisting of them.
[0070] For example, the average particle size (D 50The "average particle size (D)" may be 1 nm to 10 μm, specifically 10 nm to 2 μm, and more specifically 50 nm to 1 μm, for forming a coating layer of uniform thickness and suitable porosity. 50 )" refers to the particle size at the 50% point of the cumulative particle number distribution according to the particle size. The average particle size can be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then the dispersion medium is introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500). When the particles pass through a laser beam, the diffraction pattern difference according to the particle size is measured, and the particle size distribution can be calculated.
[0071] The porous substrate according to the present invention can provide a path for lithium ions to move while electrically insulating the negative electrode and the positive electrode to prevent short circuits, and can be a porous structure having high resistance to an electrolyte and fine pore diameters.
[0072] The porous substrate may be made of any organic or inorganic material having electrical insulation properties without any particular limitation. The porous substrate may include at least one selected from the group consisting of polyolefin, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalene, and may specifically include polyolefin. Polyolefins have excellent coating properties and can reduce the thickness of the separator, thereby increasing the proportion of the electrode active material layer in the battery and increasing the capacity per volume. Specifically, the weight average molecular weight (M w) may be 100,000 to 500,000 g / mol. If the weight average molecular weight of the polyolefin is less than the above range, it may be difficult to secure sufficient mechanical properties, and if it exceeds the above range, the shutdown function may not be realized or molding may be difficult. The shutdown function refers to the function of blocking the movement of ions and preventing thermal runaway of the battery by dissolving the thermoplastic resin and closing the pores of the porous substrate when the temperature of the secondary battery becomes high.
[0073] The thickness of the porous substrate may be, for example, 3 to 12 μm or 5 to 12 μm. If the thickness of the porous substrate is less than the numerical range, the conductive barrier function may be insufficient, and if the thickness exceeds the numerical range, the resistance of the separator may be excessively increased.
[0074] The average diameter of the pores in the porous substrate may be, for example, 10 to 100 nm. The pores in the porous substrate have an interconnected structure, allowing gas or liquid to pass from one side of the porous substrate to the other side.
[0075] The porosity of the porous substrate is not particularly limited, but may be, for example, 10 to 95%.
[0076] Positive electrode (30)
[0077] The positive electrode 30 according to the present invention may include a positive electrode current collector 30a and a positive electrode active material layer 30b disposed on at least one surface of the positive electrode current collector 30a. The positive electrode active material layer may include a positive electrode active material, a conductive material, and a positive electrode binder.
[0078] For example, the positive electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery. Specifically, the positive electrode current collector may be made of copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. The positive electrode current collector may typically have a thickness of 6 to 20 μm.
[0079] For example, the positive electrode active material may include a lithium transition metal oxide. The lithium transition metal oxide may be, for example, Li x1 CoO2(0.5 <x1<1.3)、Li x2 NiO2(0.5 <x2<1.3)、Li x3 MnO2(0.5 <x3<1.3)、Li x4 Mn2O4(0.5 <x4<1.3)、Li x5 (Ni a1 Co b1 Mn c1 )O2(0.5 <x5<1.3,0<a1<1,0<b1<1,0<c1<1,a1+b1+c1=1)、Li x6 Ni 1-y1 Co y1 O2(0.5 <x6<1.3,0<y1<1)、Li x7 Co 1-y2 Mn y2 O2(0.5 <x7<1.3,0≦y2<1)、Li x8 Ni 1-y3 Mn y3 O2(0.5 <x8<1.3,O≦y3<1)、Li x9 (Ni a2 Co b2 Mn c2 )O4(0.5 <x9<1.3,0<a2<2,0<b2<2,0<c2<2,a2+b2+c2=2)、Li x10 Mn 2-z1 Ni z1 O4(0.5 <x10<1.3、0<z1<2)、Li x11 Mn 2-z2 Co z2 O4(0.5 <x11<1.3,0<z2<2)、Li x12CoPO4 (0.5 < x12 < 1.3) and Li x13 It may be one or more selected from the group consisting of x13 FePO4 (0.5 < x13 < 1.3).
[0080] The conductive material used for the positive electrode may be the same as or different from the conductive material used for the negative electrode.
[0081] For example, the positive electrode binder may be poly(vinylidene fluoride co-hexafluoropropylene), poly(vinylidene fluoride-co-trichloroethylene), poly(methylmethacrylate), poly(ethylhexylacrylate), poly(butylacrylate), poly(acrylonitrile), poly(vinylpyrrolidone), poly(vinyl acetate), ethylene-vinyl acetate copolymer (poly(ethylene-co-vinyl acetate)), poly(ethylene oxide), polyacrylate, cellulose acetate, cellulose acetate butyrate. The cellulose acetate butyrate, cellulose acetate propionate, cyano ethyl pullulan, cyano ethyl poly(vinylalcohol), cyanoethylcellulose, cyanoethylsucrose, pullulan, and carboxyl methyl cellulose, ...
[0082] electrolyte
[0083] The electrolyte according to the present invention may include a solvent and a lithium salt.
[0084] Solvents according to the invention are, for example, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone, ethyl methyl carbonate (EMC), gamma-buturolactone (GBL), fluoroethylene carbonate (Fluoroethylene carbonate), ethylene tetrahydrofuran (Ethylene ... The alkyl group may be one or a mixture of two or more selected from the group consisting of methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, pentyl acetate, methyl propionate, ethyl propionate, ethyl propionate, and butyl propionate.
[0085] The lithium salt according to the invention is, for example, NO3 - , F - , Cl - , Br - , I - , PF6 - The anions may include, for example,
[0086] According to another embodiment of the present invention, the adhesive strength of the negative electrode to the separator may be 10 to 15 gf / 20 mm. For example, to measure the adhesive strength, one separator test piece (5 cm x 5 cm) and one negative electrode of the same specification are placed in an aluminum pouch, an electrolyte is injected, and a crosslinking reaction is induced for 30 minutes in a chamber at 40°C. After that, the wet adhesive strength of the negative electrode to the separator after one hour can be measured using a universal testing machine under a tensile speed of 150 mm / min.
[0087] The secondary battery according to the present invention may be a cylindrical, square or pouch-shaped secondary battery, but is not particularly limited as long as it corresponds to a charge / discharge device.
[0088] According to yet another embodiment of the present invention, there is provided a battery module including the secondary battery as a unit cell, and a battery pack including the battery module. The battery pack can be used as a power source for at least one medium-sized or large-sized device selected from the group consisting of a power tool, an electric vehicle (EV), a hybrid electric vehicle (HEV), and an electric vehicle (PHEV), including a plug-in hybrid electric vehicle (PHEV), or a power storage system.
[0089] 2. Manufacturing method of secondary batteries
[0090] According to yet another embodiment of the present invention, a method for manufacturing a secondary battery may be provided. The repeated descriptions of the above will be briefly described or omitted.
[0091] A method for manufacturing a secondary battery according to the present invention may include the steps of: coating at least one surface of a porous substrate with a composition for forming a coating layer, and drying the coating layer to form a separator; and forming an anode of an anode slurry on one surface of the separator.
[0092] Specifically, the composition for forming the coating layer includes an initiator and a crosslinking agent.
[0093] The initiator according to the present invention can initiate a crosslinking reaction between the binder polymer in the negative electrode and the crosslinker in the coating layer. The initiator can be, for example, a thermal initiator, and the thermal initiator can be, for example, one or more selected from the group consisting of potassium persulfate, ammonium persulfate, sodium persulfate, and potassium persulfate. For example, the content of the initiator can be 0.001 to 0.010 parts by weight based on 100 parts by weight of the binder polymer.
[0094] The crosslinking agent according to the present invention can form a crosslink with the binder polymer in the negative electrode to increase the adhesive strength of the negative electrode to the separator, effectively preventing excessive volume expansion of the negative electrode during charging and effectively preventing cracks from occurring in the coating layer of the separator during discharging, thereby effectively preventing an increase in resistance due to cell degradation.
[0095] According to another embodiment of the present invention, the content of the crosslinking agent may be 0.01 to 0.10 parts by weight, specifically 0.02 to 0.08 parts by weight, more specifically 0.03 to 0.07 parts by weight, more specifically 0.04 to 0.06 parts by weight, and more specifically 0.05 to 0.06 parts by weight, based on 100 parts by weight of the binder polymer. When the content of the crosslinking agent satisfies the above numerical range, crosslinking is sufficiently progressed, and the adhesive strength of the separator to the negative electrode on the electrolyte is sufficiently improved, and at the same time, the performance of the secondary battery can be improved.
[0096] The composition for forming a coating layer according to the present invention may further include a polymerization catalyst for controlling the rate of polymerization. The polymerization catalyst may be, for example, tetramethylethylenediamine (TEMED). For example, the content of the polymerization catalyst may be 0.001 to 0.010 parts by weight based on 100 parts by weight of the binder polymer.
[0097] Specifically, the negative electrode slurry includes a binder polymer, which may include polyacrylamide capable of suppressing a volume change of the negative electrode and cross-linking with a cross-linking agent.
[0098] According to another embodiment of the present invention, the content of the binder polymer may be 5 to 15 wt%, specifically 5 to 12 wt%, more specifically 5 to 10 wt%, and more specifically 5 to 8 wt%, based on the weight of the total solid content included in the negative electrode slurry. When the content of the binder polymer is within the above range, it can act as a binder in the negative electrode to suppress separation between the negative electrode active material particles or between the negative electrode active material layer and the current collector, and can effectively prevent volume expansion of the silicon-based negative electrode active material particles by sufficiently forming cross-linking bonds with the cross-linking agent. This can increase the adhesive strength of the negative electrode to the coating layer of the separator.
[0099] The method for manufacturing a secondary battery according to the present invention may further include the steps of forming a positive electrode on the other surface of the separator to manufacture an electrode assembly, inserting the electrode assembly into a battery case, and injecting an electrolyte into the battery case, and placing the battery case containing the electrolyte in a chamber at 40 to 80° C. to carry out a crosslinking reaction.
[0100] Specifically, the electrode assembly may be a result of compressing a laminated structure in which a negative electrode, a separator, and a positive electrode are sequentially stacked, using a compression machine such as a roll press.
[0101] Specifically, the crosslinking reaction can be carried out by placing the battery case filled with the electrolyte in a high-temperature chamber. The crosslinking reaction can be carried out for 10 to 60 minutes in a chamber at 40 to 70° C., specifically, for 20 to 40 minutes in a chamber at 40 to 60° C. When the chamber temperature for the crosslinking reaction is within the above range, crosslinking between the binder polymer in the negative electrode and the crosslinker in the composition for forming a coating layer can be effectively carried out.
[0102] Hereinafter, an embodiment of the present invention will be described in detail so that a person having ordinary skill in the art to which the present invention belongs can easily carry out the present invention. However, this is merely an example, and the scope of the present invention is not limited to the following content.
[0103] [Production Preparation Example 1: Production of negative electrode slurry]
[0104] <Comparative Preparation Example 1: Negative electrode slurry without PAM binder polymer>
[0105] Silicon negative electrode active material (D 50 = 5μm), conductive material (graphite) and binder (CMC:SBR = 1:1 (w / w)) were added to a solvent (water) in a weight ratio of 90:5:5 and stirred at 2,000 rpm for 30 minutes to prepare a negative electrode slurry with a total solid content of 50 wt%.
[0106] <Preparation Example 1: Negative electrode slurry containing PAM binder>
[0107] A negative electrode slurry was prepared in the same manner as in Comparative Preparation Example 1, but instead of the binder (CMC:SBR=1:1 (w / w)), a binder in which CMC (Carboxymethylcellulose; Mw=170,000 g / mol), SBR (Styrene-butadiene rubber), and PAM (Poly acryl amide; Mw=750,000 g / mol) were mixed in a weight ratio of 1:1:1 was used.
[0108] [Production Preparation Example 2: Production of composition for forming coating layer]
[0109] <Comparative Preparation Example 2: Composition for forming a coating layer not containing a crosslinking agent>
[0110] A particle-type acrylic binder with an average particle size of 150 nm (Tg = -20°C) and an average particle size (D 50The binder suspension was prepared by mixing inorganic particles (Al2O3) with a particle size of 0.5 μm at a weight ratio of 5:95 (binder:inorganic particles) and adding the mixture to a solvent (water). A dispersant (Carboxymethylcellulose; CMC) was added to the binder suspension so that the weight ratio of the particulate acrylic binder to the dispersant was 5:5, thereby preparing a composition for forming a coating layer with a total solid content of 30 wt%.
[0111] <Preparation Example 2: Composition for forming a coating layer containing a crosslinking agent>
[0112] A composition for forming a coating layer was prepared in the same manner as in Comparative Preparation Example 2, but 0.06 parts by weight of a crosslinker (N,N'-methylenebisacrylamide), 0.01 parts by weight of an initiator (ammonium persulfate), and 0.005 parts by weight of a polymerization catalyst (tetramethylethylenediamine; TEMED) were additionally added to 100 parts by weight of the binder polymer (PAM) of Example Preparation Example 1.
[0113] <Preparation Example 2-1: When the type of crosslinking agent is different from Preparation Example 2>
[0114] A composition for forming a coating layer was prepared in the same manner as in Preparation Example 2, but N,N'-bisacrylylcystamine was used instead of N,N'-methylenebisacrylamide.
[0115] [Production Preparation Example 3: Production of Separation Membrane]
[0116] <Comparative Preparation Example 3: Separator having a coating layer prepared using the composition for forming a coating layer according to Comparative Preparation Example 2>
[0117] The composition for forming a coating layer according to Comparative Preparation Example 2 was applied to one side of a polyethylene porous substrate having a thickness of 10 μm and a porosity of 45% by a slot-die coating method, and then dried at 60° C. for 30 minutes to form a coating layer having a thickness of 1.5 μm.
[0118] <Preparation Example 3: Separator having a coating layer prepared using the composition for forming a coating layer according to Preparation Example 2>
[0119] A separation membrane was produced in the same manner as in Comparative Preparation Example 3, but the composition for forming a coating layer according to the Working Preparation Example 2 was used instead of the composition for forming a coating layer according to Comparative Preparation Example 2.
[0120] <Preparatory Example 3-1: Separator having a coating layer prepared using the composition for forming a coating layer according to Preparatory Example 2-1>
[0121] A separation membrane was produced in the same manner as in Preparatory Example 3, but the composition for forming a coating layer according to Preparatory Example 2-1 was used instead of the composition for forming a coating layer according to Preparatory Example 2.
[0122] [Production Example 1: Production of negative electrode-separator assembly]
[0123] <Comparative Example 1: PAM binder X in negative electrode + crosslinker X in composition for forming coating layer>
[0124] Anode production
[0125] The negative electrode slurry of Comparative Preparation Example 1 was applied to a copper thin film (negative electrode current collector) having a thickness of 20 μm using a doctor blade, and then dried at 110° C. (overnight) and rolled to prepare a negative electrode (thickness: 130 μm).
[0126] Manufacturing of negative electrode-separator assembly
[0127] The separator according to Comparative Preparation Example 3 and the rolled negative electrode were stacked in this order and then lamination was performed to prepare a negative electrode-separator assembly. The separator was adjusted so that the coating layer was in contact with the rolled negative electrode. The negative electrode-separator assembly was placed in a battery case (aluminum pouch) and an electrolyte was then poured into it. The electrolyte was in the form of a solution in which 1M LiPF6 was dissolved in a carbonate-based mixed solvent in which ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 1:1.
[0128] <Comparative Example 2: PAM binder O in negative electrode + crosslinker X in composition for forming coating layer>
[0129] A negative electrode-separator assembly was prepared in the same manner as in Comparative Example 1, but the negative electrode slurry of the Working Preparation Example 1 was used instead of the negative electrode slurry of the Comparative Preparation Example 1.
[0130] <Example 1: PAM binder O in negative electrode + crosslinker O in composition for forming coating layer>
[0131] A negative electrode-separator assembly was prepared in the same manner as in Comparative Example 2, but the separator of Comparative Preparation Example 3 was replaced with the separator of Example Preparation Example 3, and the battery case filled with the electrolyte was placed in a chamber at 40° C. for 30 minutes to induce a crosslinking reaction.
[0132] <Example 2: Different type of crosslinking agent from Example 1>
[0133] A negative electrode-separator assembly was produced in the same manner as in Example 1, but the separator according to Preparative Example 3-1 was used instead of the separator according to Preparative Example 3.
[0134] [Experimental Example 1: Evaluation of adhesion between negative electrode and separator on electrolyte]
[0135] A test specimen was prepared according to the method of Preparation Example 1. In the case of Example 1, one separator test specimen (5 cm x 5 cm) and one negative electrode of the same specifications were placed in an aluminum pouch, and then an electrolyte was injected and a crosslinking reaction was induced for 30 minutes in a chamber at 40°C. After one hour, the wet adhesive strength of the negative electrode to the separator was measured using a universal testing machine at a tensile speed of 150 mm / min.
[0136] Meanwhile, in Table 1 below, the contents of the crosslinking agent and the polymerization catalyst are set based on 100 parts by weight of the binder polymer (polyacrylamide).
[0137] [Table 1]
[0138] Referring to Table 1, it can be seen that Example 1 has a significantly higher adhesive strength of the negative electrode to the separator coating layer than Comparative Examples 1 and 2. It can be inferred that the adhesive strength of the negative electrode to the separator coating layer is significantly improved because the separator coating layer and the negative electrode form a crosslinked matrix through chemical crosslinking. Comparing Examples 1 and 2 in terms of the adhesive strength between the negative electrode and separator depending on the type of crosslinker in Table 1, Example 1, which used N,N'-methylenebisacrylamide as a crosslinker, showed a higher adhesive strength between the negative electrode and separator than Example 2.
[0139] Considering the above experimental results comprehensively, according to one aspect of the present invention, a binder polymer that forms a chemical cross-linking bond with the composition for forming a coating layer is added to the negative electrode slurry, and a cross-linking agent is added to the composition for forming a coating layer, so that the binder polymer reacts with the cross-linking agent to form a cross-linked matrix at the interface between the negative electrode and the coating layer. The formation of the cross-linked matrix at the interface between the negative electrode and the coating layer of the separator can significantly increase the adhesive strength between the negative electrode and the separator on the electrolyte.
[0140] In addition, according to another aspect of the present invention, a crosslinked matrix is formed at the interface between the negative electrode and the coating layer included in the separator, thereby effectively preventing excessive volume expansion of the negative electrode during charging, and effectively preventing cracks from occurring in the coating layer of the separator during discharging, thereby preventing an increase in resistance due to cell degradation.
[0141] Although the preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concept of the present invention defined in the following claims also belong to the scope of the present invention. [Explanation of symbols]
[0142] 10 negative electrode
[0143] 20 Separation membrane
[0144] 30 positive electrode
[0145] 100 Secondary battery
Claims
1. A secondary battery comprising: a negative electrode; a positive electrode; a separator interposed between the negative electrode and the positive electrode, the separator including a porous substrate and a coating layer disposed on at least one surface of the porous substrate; and an electrolyte, the negative electrode includes a binder polymer including a first repeat unit, The coating layer comprises a second repeat unit, The first repeat unit and the second repeat unit are bonded together. Secondary battery.
2. The negative electrode contains silicon-based active material particles. The secondary battery according to claim 1 .
3. The binder polymer is Contains polyacrylamide The secondary battery according to claim 1 .
4. The coating layer is disposed between the negative electrode and the porous substrate; The secondary battery according to claim 1 .
5. the second repeat unit is derived from a crosslinker; The secondary battery according to claim 1 .
6. The crosslinking agent is A compound containing carbon-carbon double bonds at both ends. The secondary battery according to claim 5 .
7. The crosslinking agent is one or more selected from the group consisting of N,N'-methylenebisacrylamide, N,N'-bisacrylylcystamine, and N,N'-diallyltartardiamide; The secondary battery according to claim 6.
8. the first repeat unit and the second repeat unit form a crosslinked matrix; The degree of crosslinking of the crosslinked matrix is 5 to 15%; The secondary battery according to claim 1 .
9. The adhesive strength of the negative electrode to the separator is 10 to 15 gf / 20 mm. The secondary battery according to claim 1 .
10. A step of coating a composition for forming a coating layer on at least one surface of a porous substrate and then drying the composition to prepare a separator; forming an anode of the anode slurry on one surface of the separator; The composition for forming a coating layer includes an initiator and a crosslinking agent, The negative electrode slurry contains a binder polymer. A method for manufacturing a secondary battery.
11. The content of the crosslinking agent is 0.01 to 0.10 parts by weight based on 100 parts by weight of the binder polymer; The method for producing a secondary battery according to claim 10.
12. The content of the binder polymer is 5 to 15 wt % based on the weight of the total solid content contained in the negative electrode slurry, The method for producing a secondary battery according to claim 10.
13. The composition for forming a coating layer further includes a polymerization reaction catalyst. The method for producing a secondary battery according to claim 10.
14. forming a positive electrode on the other surface of the separator to manufacture an electrode assembly; inserting the electrode assembly into a battery case and then injecting an electrolyte into the battery case; and placing the battery case into which the electrolyte is injected in a chamber at 40 to 80° C. to carry out a crosslinking reaction. The method for producing a secondary battery according to claim 10.
Citation Information
Patent Citations
Lithium secondary battery
JP2013161784A
Electrode for nonaqueous electrolyte secondary battery, nonaqueous electrolyte secondary battery, and manufacturing method therefor
JP2013191550A
Pachinko game machine
JP2015003078A
Rechargeable lithium battery
JP2015037078A
Laminate, power storage device separator, power storage device, lithium ion secondary battery, and copolymer
JP2015138770A